2017
DOI: 10.1186/s40035-017-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low versus high frequency stimulation on freezing of gait and other axial symptoms in Parkinson patients with bilateral STN DBS: a mini-review

Abstract: Some studies have shown that low frequency stimulation (LFS, most commonly 60 Hz), compared to high frequency stimulation (HFS, most commonly 130 Hz), has beneficial effects, short-term or even long-term, on improving freezing of gait (FOG) and other axial symptoms, including speech and swallowing function, in Parkinson disease (PD) patients with bilateral subthalamic nucleus deep brain stimulation (STN DBS). However, other studies failed to confirm this. It seems not clear what determines the difference in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 47 publications
(157 reference statements)
2
57
0
Order By: Relevance
“…Optimization of programming parameters to reduce these stimulation‐related side effects have so far largely focused on voltage and frequency modulations, with beneficial effects reported for speech, gait, and freezing . The pulse width (PW) is another parameter that may be altered in an attempt to reduce stimulation‐induced side effects.…”
mentioning
confidence: 99%
“…Optimization of programming parameters to reduce these stimulation‐related side effects have so far largely focused on voltage and frequency modulations, with beneficial effects reported for speech, gait, and freezing . The pulse width (PW) is another parameter that may be altered in an attempt to reduce stimulation‐induced side effects.…”
mentioning
confidence: 99%
“…As suggested by our recent review, patients with FOG under routine HFS almost always benefit from the LFS 8. Almost all the studies with patients exhibiting FOG at HFS on examination showed a good response to LFS,9 10 13 14 18 23 regardless of medication off9 14 or on state,10 13 18 23 with9 14 23 24 or without adjusting the TEED 10 11 18 23 24.…”
Section: Discussionmentioning
confidence: 84%
“…Hence, 60 Hz probably would be more likely to produce a beneficial effect on FOG. It makes sense that ventral contacts, which are closer to PPNr, could be more likely to benefit from LFS,9 12 13 though this is not always the case 8. Overriding antikinetic neuronal oscillations in the beta band and enhancing the prokinetic gamma band activity by 60 Hz stimulation could also play a role in the beneficial effect of LFS 38 39.…”
Section: Discussionmentioning
confidence: 99%
“…Three recent reviews on low‐frequency STN‐DBS described beneficial effects on freezing of gait, speech, and swallowing that did not respond to, or were caused by, high‐frequency DBS. However, beneficial effects could not always be reproduced, and low‐frequency stimulation sometimes led to worsening of cardinal PD symptoms . The effect of variable frequency stimulation, a paradigm interleaving high‐ and low‐frequency DBS, will be explored soon …”
Section: Future Considerationsmentioning
confidence: 99%
“…However, beneficial effects could not always be reproduced, and low-frequency stimulation sometimes led to worsening of cardinal PD symptoms. [87][88][89] The effect of variable frequency stimulation, a paradigm interleaving high-and low-frequency DBS, 90 will be explored soon. 91 Also, pulse-width modulation might provide clinical benefit in certain situations.…”
Section: Adbs Modulation Other Than Amplitude Modulationmentioning
confidence: 99%